Design and numerical analysis of steel frame joints with replaceable buckling-restrained links. (September 2022) - Feng, Yulong; Wei, Mingtu; Chong, Xun; Jiang, Qing; Zhu, Yi
Abstract: This paper proposes a steel frame joint with a replaceable buckling-restrained link to prevent the buckling of joint plates and enhance the seismic performance. The calculation formulas of the yield load and initial stiffness are derived to determine a theoretical skeleton curve. A design method for the joints is proposed to determine the design parameters of the core plate area and length, ear and end plate thicknesses, and restraining plate thicknesses, based on the design conditions of the designed joint yield load and core plate strain limited values, plate deformation limited values, and restraining ratios, respectively. The derived formulas and design method are verified by analyzing the results of a cyclic loading test and 37 parametric numerical models calibrated with the test results. The results show that the theoretical skeleton curve is in good agreement with the test and numerical results, and the performances of the joints designed using the proposed method are close to the design conditions, implying the satisfactory performance of the design theory. The influences of the design parameters on the joint are well reflected by the parametric analysis Graphical abstract: Unlabelled Image Highlights: A novel earthquake-resilient steel joint with a replaceable buckling-restrained link is proposed. The calculation formulas of the theoretical skeleton curve and design method for the proposed joint are established. A cyclic loading test and 37 parametric numerical models are used to verify the derived formulas and design method. The influences of the design parameters on the joint are investigated by parametric numerical models.